Potret Pekerja Kerajinan Seni Ukir Relief Jepara - Alamsyah Alamsyah (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
The existence of relief carvings in Jepara is marked by the presence of white coral ornaments found in the Mantingan Mosque. These ornaments show that the craft of relief carving has been around for hundreds of years in Jepara. The existence and development of relief carvings are thanks to the contributions of workers or relief engravers. With the ability to carve it out, they can preserve and develop this craft. Most of the relief carving skills were obtained from the apprenticeship process from the carver that had been around his house since he was in elementary school. A sculptor needs a long process to become a relief engraver because of not all engravers can be relief engravers. The ability of the relief engraver was getting better after the establishment of the Technical School in the 1930s. Relief engravers who get a formal education will be able to integrate self-taught and theoretical abilities. The development of relief carving art grew rapidly during the independence period, the new order, and the reform order. Relief engravers need high carving abilities and complicated technical abilities so they can carve a fragment of a story or theme and have a naturalist pattern. At the beginning of the 21st century, the number of relief engravers was fewer and dominated by the older generation because the younger generation was reluctant to learn carving. Although relief engravers are increasingly scarce, their skills have not been rewarded with high wages.